Cases of Lyme Disease Appear to Follow Periodic Cycles Linked to Geography - Van Pelt, Nicholas; Marshall, Jeremy (My University, 2018)
We are studying the spread of Lyme disease through Wisconsin. It is important because the number of people diagnosed with Lyme Disease in the US is around 300,000, annually (CDC 2017). The CDC has collected data of reported Lyme Disease cases since 2001. When looking at the data we noticed that the trends of cases of Lyme disease followed a cyclical pattern. The cycles varied widely. We hypothesized that environmental and geographical factors could affect the main vector of Lyme Disease, Ixodes scapularis (the black-legged tick). After analyzing Lyme Disease data from the CDC and using a map making software (Paint Maps 2018), we found that geographical distribution had a marked effect on the rate at which counties cycled between up and down trends in infection rates. These findings are important because they give us more insight into possible control methods to keep the black-legged tick, and therefore Lyme Disease, at a manageable level.
Keywords: Fall 2018